ANALISIS KEARIFAN LOKAL TANAMAN BUAH SALAK DI KECAMATAN ANGKOLA BARAT KABUPATEN TAPANULI SELATAN PROVINSI SUMATERA UTARA - Rifsan Azizi; Eri Sayamar; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Commodities bark (zalacca edulis) is a plant that is suitable to be developed in Indonesia. The purpose of this study are: (1) To identify the forms of local wisdom in crops of fruits from the first until now. (2) To determine the application of indigenous crops of fruits in the District of West Angkola. (3) To know the strategy in maintaining local knowledge in plant fruits. This study using interviews, questionnaires and Snowball Sampling in the number of respondents the right to obtain 15 respondents consisting of 1) village officials, 2) Elders (Datuk), 3) Religious Leaders, 4) Figures Supernatural, 5) Community Leaders, 6 ) Farmer Members, 7) Parent, 8) Agricultural extension field, 9) Vegetable Bark. In the amount of local knowledge by the farmers of fruits ago and is now at 55 local wisdom Identification. Local knowledge of plant fruits dominated by the activity pattern of human behavior, behavior, actions / activities that reflect the daily life of the local community and religion. Keywords: Local Wisdom, Identification, Farmer